Epilepsy surgery in children and adolescents with malformations of cortical development–outcome and impact of the new ILAE classification on focal cortical dysplasia - Muehlebner, Angelika; Groeppel, Gudrun; Dressler, Anastasia; Reiter-Fink, Edith; Kasprian, Gregor; Prayer, Daniela; Dorfer, Christian; Czech, Thomas; Hainfellner, Johannes A.; Coras, Roland; Blümcke, Ingmar; Feucht, Martha (Epilepsy Research, 2014)
To determine long-term efficacy and safety of epilepsy surgery in children and adolescents with malformations of cortical development (MCD) and to identify differences in seizure outcome of the various MCD subgroups. Special focus was set on the newly introduced International League Against Epilepsy (ILAE) classification of focal cortical dysplasia (FCD).This is a single center retrospective cross-sectional analysis of prospectively collected data.age at surgery <18 years, pre-surgical evaluation and epilepsy surgery performed at the Vienna pediatric epilepsy center, histologically proven MCD, complete follow-up data for at least 12 months. Clinical variables evaluated: type and localization of MCD, type of surgery and a variety of clinical characteristics reported to be associated with (un-)favorable outcomes. MCD were classified following the existing classification schemes (Barkovich et al., 2012. Brain. 135, 1348-1369; Palmini et al., 2004. Neurology. 62, S2-S8) and the ILAE classification for FCD recently proposed by Blümcke in 2011. Seizure outcome was classified using the ILAE classification proposed by Wieser in 2001.60 Patients (51.7% male) were included. Follow up was up to 14 (mean 4.4 ± 3.2) years. Mean age at surgery was 8.0 ± 6.0 (median 6.0) years; mean age at epilepsy onset was 2.9 ± 3.2 (median 2.0) years; duration of epilepsy before surgery was 4.8 ± 4.4 (median 3.0) years. 80% of the patients were seizure free at last follow-up. AEDs were successfully withdrawn in 56.7% of all patients. Extended surgery, lesion localization in the temporal lobes and absence of inter-ictal spikes in postsurgical EEG recordings were predictive of favorable seizure outcomes after surgery. However, no association was found between outcome and MCD sub-types. Epilepsy surgery is highly effective in carefully selected drug-resistant children with MCD. Surrogate markers for complete resection of the epileptogenic zone remain the only significant predictors for seizure freedom after surgery.
EVALuna2:7258